A trading post for marine products - Perez, Romeo S. (Manila : National University, 2000)
The trading post for a marine products is a necessary component of the government avowed objective of providing a steady and sufficient supply of marine products at reasonable prices. It makes this possible by providing the necessary post harvest facilities to insure that newly hauled marine products are handle properly and expeditiously at least coast.
Title page -- Letter of endorsement -- Jury's Approval sheet -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Analysis -- Chapter IV. Conclusion and recommendation -- Bibliography -- Appendices -- Profile of proponent.
Includes bibliographical references.
Keywords: MARINE PRODUCTS